2009
DOI: 10.1038/onc.2008.495
|View full text |Cite|
|
Sign up to set email alerts
|

Regulation of microRNA expression by HMGA1 proteins

Abstract: The High Mobility Group proteins HMGA1 are nuclear architectural factors that play a critical role in a wide range of biological processes. Since recent studies have identified the microRNAs (miRNAs) as important regulators of gene expression, modulating critical cellular functions such as proliferation, apoptosis and differentiation, the aim of our work was to identify the miRNAs that are physiologically regulated by HMGA1 proteins. To this purpose, we have analysed the miRNA expression profile of mouse embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 60 publications
1
44
0
2
Order By: Relevance
“…However, and in common with protein-coding genes, miRNAs can be silenced through aberrant hypermethylation of CpG islands and/or by histone modifications. [18] Irrespective of pituitary adenoma subtype a significant proportion overexpress HMGA1 and HMGA2 [33,10,34,35], indeed, in the cohort we now describe, similar conclusions are apparent (data not shown). Convincing evidence for the role of these genes, and their protein products, in tumour evolution are provided through studies in transgenic mice, where, enforced expression of either hmga1 or hmga2 leads to the development of pituitary adenomas.…”
Section: Discussionsupporting
confidence: 75%
“…However, and in common with protein-coding genes, miRNAs can be silenced through aberrant hypermethylation of CpG islands and/or by histone modifications. [18] Irrespective of pituitary adenoma subtype a significant proportion overexpress HMGA1 and HMGA2 [33,10,34,35], indeed, in the cohort we now describe, similar conclusions are apparent (data not shown). Convincing evidence for the role of these genes, and their protein products, in tumour evolution are provided through studies in transgenic mice, where, enforced expression of either hmga1 or hmga2 leads to the development of pituitary adenomas.…”
Section: Discussionsupporting
confidence: 75%
“…Moreover, it is noteworthy that these five miRNAs were associated by the web system to 57 cellular processes, including those in which HMGA proteins have been previously demonstrated to be involved, such as cell proliferation, differentiation, DNA-repair, chromatin modification and regulation of transcription (Fusco and Fedele, 2007;. The direct targeting of HMGA1 by miR-16 (Kaddar et al, 2009), and of HMGA2 by Let-7a (Lee and Dutta, 2007) and miR196ab (De Martino et al, 2009a) was previously reported. Moreover, previous studies showed that miR-26a regulates HMGA2 expression (Lee et al, 2011).…”
Section: Identification Of Hmga-targeting Mirnasmentioning
confidence: 99%
“…The 3 0 -UTR region of HMGA2 gene, including binding sites for miR-15, miR16, miR26ab, miR-196a and let-7a was previously described (De Martino et al, 2009a). The 3 0 -UTR region of the HMGA1 gene, including binding sites miR-15, miR16, miR26ab, miR-196a and let-7a was amplified by PCR from human genomic DNA by using the following primers:…”
Section: Plasmids and Constructsmentioning
confidence: 99%
See 2 more Smart Citations